The role of organizational learning in achieving the competitive capacity of the organization - علاء فرحان طالب; علي كريم عبدالسالم الخفاجي; محمد جبار هادي (Iraqi Journal for Administrative Sciences, 2024)
I have dealt with study the role of organizational learning in achieving the competitive capabilities of the organization, where we see the challenges facing organizations today dictate now and in the future activation of scientific expertise to meet these challenges and the dissemination of these concepts within the priorities and data organizational culture of these organizations despite having a lot of knowledge and learning applications .Despite the importance of organizational learning and adopting some of the organizations have to enhance their competitiveness, we find a lot of organizations, including organizations (universities researched) still do not realize the importance of the role of organizational learning in achieving competitiveness, here identified the problem of study focus has been to develop suitable solution her as much as possible . And this study has sought to achieve a number of goals, most notably: to know the extent of adoption of the researched universities (study population) for organizational learning in its various dimensions in strengthening their competitiveness, and to determine correlations between organizational learning and competitiveness of universities. In this context, the formulation of two main premises were as follows (do not vary the concerns of universities discussed in the adoption of the study variables (f) There is no relationship statistically significant correlation between organizational learning and competitiveness of universities), and (no effect relationship of statistical significance between organizational learning, and the competitiveness of universities). And have reached several conclusions to the study of which was most important (vary the interest of universities discussed in the adoption of the study variables) and the existence of linkages and the impact of moral and statistical significance between the variable of the study and to varying degrees. . These included the study several recommendations, including (the necessity of adopting universities researched building a comprehensive organizational learning dimensions of all) and to disseminate the culture of learning in universities, and provide a more hospitable environment recognizes the importance of organizational learning in universities, and attention to draw the necessary strategies to develop the knowledge faculty and their creative and disclosure future serve as investment knowledge.